Electrocoagulation of Rhodamine B Dye Using Zinc Electrodes - Refinel; Sari, Berliana Mayang; Emriadi (Departemen Kimia Universitas Andalas, 2025)
The textile wastewater containing Rhodamine B is difficult to degrade naturally and poses serious environmental threats. This study evaluated the effectiveness of electrocoagulation using zinc electrodes for Rhodamine B removal. Variables analyzed were concentration, pH, time, voltage, and electrode distance. Removal efficiency was measured using UV-Vis spectrophotometry at λ 545 nm, while FTIR characterization confirmed molecular changes. The optimum condition was obtained at 75 min, pH 6, 5 V, and 1 cm electrode distance, resulting in 98.68 % removal efficiency. FTIR spectra supported the successful removal of Rhodamine B. This demonstrates that electrocoagulation with zinc electrodes is an effective and eco-friendly method for textile wastewater treatment.